2014
DOI: 10.1016/j.molimm.2013.10.007
|View full text |Cite
|
Sign up to set email alerts
|

Membrane pore formation by human complement: Functional importance of the transmembrane β-hairpin (TMH) segments of C8α and C9

Abstract: Human C8 and C9 have a key role in forming the pore-like “membrane attack complex” (MAC) of complement on bacterial cells. A possible mechanism for membrane insertion of these proteins was suggested when studies revealed a structural similarity between the MACPF domains of the C8α and C8β subunits and the pore-forming bacterial cholesterol-dependent cytolysins (CDCs). This similarity includes a pair of α-helical bundles that in the CDCs refold during pore formation to produce two transmembrane β-hairpins (TMH1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…Interestingly, the C8β N243 glycosylation is in the C8β MACPF domain. These MACPF domains undergo a large conformational change when the soluble C8 is incorporated into the MAC [ 42 ]. Especially, the transmembrane β-hairpin (TMH) segments play a direct role in MAC membrane penetration.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, the C8β N243 glycosylation is in the C8β MACPF domain. These MACPF domains undergo a large conformational change when the soluble C8 is incorporated into the MAC [ 42 ]. Especially, the transmembrane β-hairpin (TMH) segments play a direct role in MAC membrane penetration.…”
Section: Discussionmentioning
confidence: 99%
“…Recent experiments involving chimeric complement proteins provide further experimental evidence that the predicted TMH segments of C8 and C9 are directly involved in membrane penetration and pore formation. 44 Cryo-EM reconstructions of CDC prepore and pore complexes 45 together with fluorescence-based biophysical data 46 have provided key insights into how MACPF domains are arranged in membranes (Figure 4C). For the majority of CDCs, association with cholesterol through domain 4 (lacking in complement components) is allosterically coupled to large conformational changes in the CDC/MACPF domain during pore formation.…”
Section: ■ Macpf Pore Formation and Lessons From A Bacterial Model Sy...mentioning
confidence: 99%
“…The segments in C9 are longer still and possess a hydrophilic loop at the tip, which may interact with intracellular proteins or anchor the pore to the cytoplasm. Recent experiments involving chimeric complement proteins provide further experimental evidence that the predicted TMH segments of C8 and C9 are directly involved in membrane penetration and pore formation …”
Section: Macpf Pore Formation and Lessons From A Bacterial Model Systemmentioning
confidence: 99%
“…Complement activation by the complement component 3 (C3) and complement component 5a (C5a) fragments are associated with pregnancy loss showing complement activation can adversely affect pregnancy. C8 and C9 are activated in the final steps to form pores on target cells and induce cell death by contributing to the membrane attack complex (MAC) [24]. Complement component 8 (C8) and complement component (C9) were observed as ambiguously regulated in two studies, one serum source reported C8 and C9 as down regulated at delivery while the other reported up-regulated but the gestational age of the samples was not reported (Table2 and Supplementary Table 1) also ambiguous was Complement factor H-1 related protein, which was previously identified as a potential biomarker for preeclampsia [4].…”
Section: Immune Responsementioning
confidence: 99%